Potential energy-assisted coupling of phase change materials with triboelectric nanogenerator enabling a thermally triggered, smart, and self-powered IoT thermal and fire hazard sensor: Design, fabrication, and applications. (1st December 2022) - Yusuf, Abdulmalik; Sánchez del Río, José; Ao, Xiang; Olaizola, Ignacio Astarloa; Wang, De-Yi
Abstract: Thermal and Fire hazards result in numerous damage to human life and property. The early detection and instant communication of potential hazards using environmentally sustainable sensors before they occur would significantly reduce the negative impact on the environment while saving lives and property from destruction. Here-in, for the first time, a self-powered thermal and fire hazard sensor was designed by coupling gravitational potential energy to the triboelectric effect to generate electric signals. Harnessing the mechanical integrity and phase change property of the paraffin rod, it is employed as mechanical load support and thermal receptor in the sensor. Furthermore, the sensor was integrated with several communication interfaces such as liquid crystal display (LCD), Wi-Fi emitter, light-emitting diode (LED) light, IoT network, and mobile phone. The sensor exhibited an instant response (∼0 s response time) at temperature ranges between 80 and 89 °C. Graphical Abstract: Fire and thermal hazards claim multiple lives and cause economic sabotage daily across the globe in addition to the negative environmental impact such as smoke and toxic gases released to the environment. The early detection and instantaneous warning communication of thermal and fire hazards before damage using smart, low-cost thermal and fire hazard sensors based on renewable energy sources holds high prospects to significantly reduce the negative impact associated with fire hazards while saving multiple lives. ga1 Highlights: Self-powered thermal hazard sensor is fabricated. Potential energy is employed as assisting force. 3D Electric vehicle simulation is presented. LCD screen, Mobile phone, Wi-Fi and IoT network integration.